A STUDY OF EFFECTIVENESS COOPERATIVE LEARNING MODELS IN EFL CLASSROOM - Riski Rahmadani Harahap; Makhroji Makhroji; Evi Zulida; Fadlia Fadlia; Chairuddin Chairuddin (Universitas Samudra, 2021)
Using the right technique to teach writing descriptive text is very important to help students overcome problems in writing. Think-Pair-Share Technique is a kind of cooperative learning technique. This technique encourages students to actively involve in the learning process since they have to discuss with their partner about the material being learned. This research was conducted with qualitative research design type library research, to find out the effectiveness of Think Pair Share (TPS) technique in Students’ Writing Skills in Descriptive Text. The instrument of this research is books, journal, and other documents. The qualitative data were analyzed by using four stages suggested by Miles and Huberman. The data that has been obtained then analyzed and concluded in order to obtain conclusions about literary studies. Based on qualitative data, The result of the research showed that there is a positive effect of think pair share in writing descriptive text and for the class situation on the learning process.